Resilience and exclusion: Development policy implications - von Braun, Joachim; Thorat, Sukhadeo (International Food Policy Research Institute, 2014)
Resilience is a desirable capability of people to deal with shocks without significant loss of livelihood, health, and nutrition. Resilience is impaired by exclusion and other forms of discrimination. Exclusion is part of a larger set of causal factors that determine marginality, which is a root cause of poverty and inequality.